Branch Retinal Vein Occlusion in Factor V Leiden Mutation - Yan Tong Koh; Srinivasan Sanjay (Journal of Ophthalmic Science, 2015)
A previously healthy 25 year old Chinese male presented with left eye blurring of vision and was diagnosed to have left eye branch retinal vein occlusion. Initial blood investigations and thrombophilia screen were negative. The patient subsequently improved with observation and conservative management, with no further events over a 2 year follow up period. The blood investigations were repeated 2 years later as part of a health check-up and he was then tested to be heterozygous for the factor V leiden mutation. This was confirmed by sequencing of his genome that identified the mutation. The laboratory was contacted to provide details regarding the testing methods and was noted to have performed the two tests via different methods. While false negative rates in genetic testing are low, we believe that there is greater need to standardize testing methods as ascertaining genetic conditions play a great role in clinical diagnosis, treatment and prognosis. Clinicians should be aware of the limitations of these tests. When clinical suspicion is high, there may be a role for repeat tests with different methods or in different laboratories.
Keywords: Thrombosis